Exosomes as a Novel Approach to Reverse Osteoporosis: A Review of the Literature - Xie, Xudong; Xiong, Yuan; Panayi, Adriana C.; Hu, Liangcong; Zhou, Wu; Xue, Hang; Lin, Ze; Chen, Lang; Yan, Chenchen; Mi, Bobin; Liu, Guohui (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoporosis is a chronic disease requiring long-term, sometimes lifelong, management. With the aging population, the prevalence of osteoporosis is increasing, and with it so is the risk of hip fracture and subsequent poor quality of life and higher mortality. Current therapies for osteoporosis have various significant side effects limiting patient compliance and use. Recent evidence has demonstrated the significant role of exosomes in osteoporosis both in vivo and vitro. In this review, we summarize the pathogenesis of senile osteoporosis, highlight the properties and advantages of exosomes, and explore the recent literature on the use of exosomes in osteogenesis regulation. This is a very helpful review as several exosomes-based therapeutics have recently entered clinical trials for nonskeletal applications, such as pancreatic cancer, renal transplantation, and therefore it is urgent for bone researchers to explore whethere exosomes can become the next class of orthobiologics for the treatment of osteoporosis.